The Complex Interplay of Prematurity, Respiratory Distress Syndrome, and Necrotizing Enterocolitis: Insights from a Case Study - Putu Cahya Chandranita; I Gede Deden Susma Sugara (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Necrotizing enterocolitis (NEC) remains a devastating inflammatory bowel disease predominantly affecting premature infants, carrying significant morbidity and mortality risks. Respiratory distress syndrome (RDS), common in this population, is increasingly recognized not just as a comorbidity but as a potential contributor to NEC pathogenesis, possibly through mechanisms involving gut hypoperfusion. Understanding the clinical progression and management challenges when these conditions coexist is crucial. Case presentation: We present the case of a female infant born prematurely at 33-34 weeks gestation with a birth weight of 2280g. The infant developed early RDS, requiring Continuous Positive Airway Pressure (CPAP) support shortly after birth. On the second day of life, while RDS symptoms were improving, the infant developed signs suggestive of NEC, including abdominal distension, bilious gastric residuals, and subsequent irritability and feeding intolerance. The diagnosis of NEC (suspected Bell's stage II) was supported by clinical findings and radiological evidence of bowel wall thickening. Blood cultures identified Klebsiella pneumoniae. Initial antibiotic therapy proved insufficient, necessitating a change to meropenem and amikacin based on sensitivity testing. The infant was managed conservatively with bowel rest, parenteral nutrition, and targeted antibiotics, showing gradual clinical improvement. Enteral feeding with breast milk was successfully reintroduced, and the infant was discharged in good condition after 15 days of NICU care. Conclusion: This case highlights the challenging clinical scenario where early-onset RDS in a premature, low-birth-weight infant precedes the development of NEC. It underscores the importance of high clinical suspicion for NEC even as respiratory status improves, the utility of microbial surveillance and sensitivity testing in guiding antibiotic therapy, and the potential for successful conservative management in NEC Bell's stage II. The interplay between RDS-induced physiological stress and intestinal vulnerability likely contributed to NEC development in this patient.